Antenatal smoking and substance‐misuse, infant and newborn response to hypoxia. Issue 5 (10th October 2016) - Ali, Kamal; Rosser, Thomas; Bhat, Ravindra; Wolff, Kim; Hannam, Simon; Rafferty, Gerrard F.; Greenough, Anne
Summary: Objectives: To determine at the peak age for sudden infant death syndrome (SIDS) the ventilatory response to hypoxia of infants whose mothers substance misused in pregnancy (SM infants), or smoked during pregnancy (S mothers) and controls whose mothers neither substance misused or smoked. In addition, we compared the ventilatory response to hypoxia during the neonatal period and peak age of SIDS. Working hypothesis: Infants of S or SM mothers compared to control infants would have a poorer ventilatory response to hypoxia at the peak age of SIDS. Study Design: Prospective, observational study. Patient‐subject selection: Twelve S; 12 SM and 11 control infants were assessed at 6–12 weeks of age and in the neonatal period. Methodology: Changes in minute volume, oxygen saturation, heart rate, and end tidal carbon dioxide levels on switching from breathing room air to 15% oxygen were assessed. Maternal and infant urine samples were tested for cotinine, cannabinoids, opiates, amphetamines, methadone, cocaine, and benzodiazepines. Results: The S and SM infants had a greater decline in minute volume ( P  = 0.037, P  = 0.016, respectively) and oxygen saturation ( P  = 0.031) compared to controls. In all groups, the magnitude of decline in minute volume in response to hypoxia was higher in the neonatal period compared to at 6–12 weeks ( P  < 0.001). Conclusions: Both maternal substance misuse and smoking were associated with an impaired response to a hypoxic challenge at the peak age for SIDS. The hypoxic ventilatory decline was more marked in the neonatal period compared to the peak age for SIDS indicating a maturational effect.Pediatr Pulmonol. 2017;52:650–655. © 2016 Wiley Periodicals, Inc.